Image encryption scheme based on block‐based confusion and multiple levels of diffusion - Brindha Murugan; Ammasai Gounden Nanjappa Gounder (IET Computer Vision, 2016)
This study proposes a chaos‐based image encryption scheme using Henon map and Lorenz equation with multiple levels of diffusion. The Henon map is used for confusion and the Lorenz equation for diffusion. Apart from the Lorenz equation, another matrix with the same size as the original image is generated which is a complex function of the original image. This matrix which is configured as a diffusion matrix permits two stages of diffusion. Due to this step, there is a strong sensitivity to input image. This encryption algorithm has high key space, entropy very close to eight (for grey images) and very less correlation among adjacent pixels. The highlight of this method is the ideal number of pixels change rate and unified average changing intensity it offers. These ideal values indicate that the encrypted images produced by this proposed scheme are random‐like. Further, a cryptanalysis study has been carried out to prove that the proposed algorithm is resistant to known attacks.